2015
DOI: 10.1007/s13224-015-0815-5
|View full text |Cite
|
Sign up to set email alerts
|

Return to the Operation Theatre: An Analysis of Repeat Surgeries in Operative Obstetrics

Abstract: About the Author AbstractPurpose To determine the risk factors and associated comorbidities with a relaparotomy after primary surgery in pregnant mothers and to identify preventable causes.Methods A retrospective observational study was done at a tertiary care centre from January 2009 till August 2014. All records of exploratory laparotomy following primary surgery in the obstetric population during this period were retrieved from the hospital database and analysed. Results The incidence of relaparotomy was 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 11 publications
1
17
1
Order By: Relevance
“…7 Another study from tertiary care urban hospital has shown incidence of relap to be 0.22%. 4 In this study, obstructed labour was the commonest indication for primary cesarean similar to study by Seal SL et al 6 Second stage cesarean is technically difficult with increased chances of extension of uterine incision of fragile and edematous lower uterine segment. Second stage cesarean section when done by less skilled obstetricians thus have more chances of bleeding from extension of uterine incision, hematoma formation or intraperitoneal hemorrhage requiring relaparotomy.…”
Section: Figure 1: Maternal Mortalitysupporting
confidence: 76%
See 4 more Smart Citations
“…7 Another study from tertiary care urban hospital has shown incidence of relap to be 0.22%. 4 In this study, obstructed labour was the commonest indication for primary cesarean similar to study by Seal SL et al 6 Second stage cesarean is technically difficult with increased chances of extension of uterine incision of fragile and edematous lower uterine segment. Second stage cesarean section when done by less skilled obstetricians thus have more chances of bleeding from extension of uterine incision, hematoma formation or intraperitoneal hemorrhage requiring relaparotomy.…”
Section: Figure 1: Maternal Mortalitysupporting
confidence: 76%
“…Third case was found to have massive ascites on relap, who finally succumbed to death. Mortality rate in other studies vary from as low as 2.8% in study by Ahmed et al to high rate of 12.1% and 15.78% 4,6,12.…”
mentioning
confidence: 79%
See 3 more Smart Citations